2013
DOI: 10.5812/traumamon.8271
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Aneurysm of the Splenic Artery: A Rare Cause of Abdominal Pain after Blunt Trauma

Abstract: IntroductionSplenic artery aneurysms (SAAs) are rare (0.2-10.4%); however, they are the most common form of visceral artery aneurysms. Splenic artery aneurysms are important to identify, because up to 25% of the cases are complicated by rupture. Post- rupture mortality rate is 25% -70% based on the underlying cause. Herein we present a young patient with abdominal pain after blunt abdominal trauma due to rupture of an SAA.Case PresentationA 27-year-old male, without a remarkable medical history, who suffered f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The aneurismal rupture is the biggest threat to the patients with aneurysm at the initial portion of splenic artery. The aneurismal rupture tends to manifest as acute abdominal pain, which sometimes radiates to the back or shoulder, quick drop of blood pressure and the fast pulse rate, rapidly-progressive hemorrhagic shock or even sudden death [2,14] . Khoshnevis et al [14] reported an incidence of aneurysm rupture of 25% and a mortality rate of 25%-70%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aneurismal rupture is the biggest threat to the patients with aneurysm at the initial portion of splenic artery. The aneurismal rupture tends to manifest as acute abdominal pain, which sometimes radiates to the back or shoulder, quick drop of blood pressure and the fast pulse rate, rapidly-progressive hemorrhagic shock or even sudden death [2,14] . Khoshnevis et al [14] reported an incidence of aneurysm rupture of 25% and a mortality rate of 25%-70%.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true when the diameter of an aneurysm is larger than 2 cm and is clinically symptomatic, or when the patient involved is ready for liver transplantation or pregnancy [3,[12][13][14]17] , or when a patient with an aneurysm at the initial portion of splenic artery has concomitant multiple splenic aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 However, in the setting of trauma and emergencies, it is less suitable and instead surgical ligation of the aneurysm is more appropriate. 5 Surgical ligation was performed in almost half of our study population (45%).…”
Section: Treatment Of Splenic Artery Aneurysms In Traumamentioning
confidence: 99%
“…Mortality following rupture is generally between 25% and 70%. 4,5 Therefore, it is very important to recognize these lesions, especially in settings where there is a significant risk of rupture as intervention could be lifesaving.…”
mentioning
confidence: 99%
“…Managing patients with VT is crucial [21,22]. These patients should be treated at eth soonest possible [23].…”
Section: Introductionmentioning
confidence: 99%